The effect of problem based learning model on critical thinking skills in the context of chemical reaction rate - Daud - Dakabesi; Isana Supiah Yosephine Luoise (Journal of Education and Learning (EduLearn), 2019)
The previous research result showed that the learning model based on the investigation could increase the students’ critical thinking skills. The aim of this research was to measure the effectiveness of the using of problem-based learning model to increase the students’ critical thinking skills. The research design was quasi-experiment by using post-test only design. The population of this research was the eleventh grade students of science which contained 124 students of SMAN 6 and SMAN 7 Kupang that were chosen randomly. The treatment that was given in this research was problem-based learning model for the experiment class and conventional model for the control class whereas the given materials were the reaction rate. The learning process in the experimental class begins with the provision of contextual problems aimed at increasing students' interest and motivation in finding and designing solutions to solve problems individually or in groups. The instrument that was used in this research previously validated by two experts of theory and material. The result of this research showed that the students who studied in experiment class had different critical thinking skills better that the students who studied using conventional model.